Presidentialization of Electorate’s Behavior in the Election to Voivodeship Sejmiks in 2018 - Peszyński, Wojciech (Political Preferences, 2019)
The main category in this article is electoral presidentialization, understood as a tendency of voters’ behavior to mirror the decisions typical for presidential elections. Here, the category under consideration is analyzed in two dimensions: leader effect and social approval for the organization of television debates of the leaders of two most important parties. The author explains the process in question on the basis of quantitative and percentage distribution of answers to two questions to be found in three editions of the nation-wide electorate study “Political Preferences”. This article concerns voters’ preferences in a survey that was conducted just after the self-government election in 2018. In order to grasp the specificity of electoral behavior in this particular voting, the analysis was conducted in a comparative manner, and the subject of comparison was the 2015 election to the Sejm. The results of studies organized in 2012 and 2013, when no election was organized in Poland, were also referred to in a necessary scope.